2020
DOI: 10.1155/2020/8838524
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA/Circular RNA-miRNA-mRNA Axes in Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury (IRI) elicits tissue injury involved in a wide range of pathologies. Multiple studies have demonstrated that noncoding RNAs (ncRNAs), including long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs), participate in the pathological development of IRI, and they may act as biomarkers, therapeutic targets, or prognostic indicators. Nonetheless, the specific molecular mechanisms of ncRNAs in IRI have not been completely elucidated. Regulatory networks among lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 150 publications
1
17
0
Order By: Relevance
“…Previous studies indicated that circRNA acts as an miRNA sponge through competitive binding, consequently leading to loss of function of target miRNA and affect gene expression at the post-transcriptional level (15)(16)(17)(18)(19). In the present study, the results of the luciferase reporter assay revealed the interaction between circ_0008932 and miR-145-5p.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies indicated that circRNA acts as an miRNA sponge through competitive binding, consequently leading to loss of function of target miRNA and affect gene expression at the post-transcriptional level (15)(16)(17)(18)(19). In the present study, the results of the luciferase reporter assay revealed the interaction between circ_0008932 and miR-145-5p.…”
Section: Discussionsupporting
confidence: 54%
“…According to the admitted hypothesis, lncRNA indirectly regulates the mRNA expression by competitively interacting with miRNA ( Bao et al, 2018 ; Gong et al, 2020 ). In this article, we constructed our ceRNA network as follows ( Campbell and Khatri, 2020 ): predicting possible lncRNAs that interact with miRNA by using prediction modules of DIANA-LncBase Predicted V.2 database ( Paraskevopoulou et al, 2016 ) and forming pairwise relations between lncRNA and miRNA; the interacting score of prediction modules higher than 0.7 considered as eligible ( Donnan et al, 2008 ); miRWalk ( Dweep et al, 2011 ) 3.0, miRDB ( Chen and Wang, 2019 ), and TargetScan ( Agarwal et al, 2015 ) (Version 7.2), were used to predict the interaction between miRNAs and mRNAs, and the interacting score higher than 0.95 was regarded as eligible ( Emberson et al, 2014 ); lncRNAs and mRNAs predicted by previous two steps were matched with DElncRNAs and DEmRNAs, and only overlapped lncRNA–miRNA and mRNA–miRNA relationships were selected ( Kopp and Mendell, 2018 ); arranging these paired matched relationships, the ultimate lncRNA–miRNA–mRNA network was formed and visualized through Cytoscape (Version 3.8.0).…”
Section: Methodsmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are defined as transcripts that are longer than 200 nucleotides and are unable to encode proteins ( Kopp and Mendell, 2018 ). They were previously considered as “junk” in the mammal genome but now are found to function as a transcriptional regulator or post-transcriptional regulator: in the former, lncRNA combines with chromosomes and modifies the gene expression ( Ulitsky and Bartel, 2013 ), whereas in the latter, lncRNA can either directly impact the gene expression by regulating the degradation of genes or works as competing endogenous RNA (ceRNA) and sponge-specific miRNAs, thus indirectly regulating the gene expression ( Bao et al, 2018 ; Gong et al, 2020 ). Recently, aberrant expression of lncRNA has been reported to correlate with the onset, progression, and prognosis of acute ischemic stroke (AIS) ( Bai et al, 2014 ; Feng et al, 2019 ; Li et al, 2020a ; Wang et al, 2020a ; Fu et al, 2021 ); thus they are potential candidates for stroke diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in different pathologies correlated with oxidative stress, these regulatory mechanisms have begun to take center stage [ 224 ] In I-R, miRNAs have great advantages when used as a therapeutic target. In the future, they could be considered pharmacological approaches in clinical practice [ 255 ]. Noncoding RNA similar to miR-92a has a proangiogenic effect, and miR-499 can decrease damage induced by hypoxia-reoxygenation.…”
Section: Ischemia-reperfusion Antioxidant Pharmacodynamicsmentioning
confidence: 99%